REVISÃO DA VIDA TODA: A POSSIBILIDADE DA INCLUSÃO NOS ATUAIS BENEFÍCIOS PREVIDENCIÁRIOS DE CONTRIBUIÇÕES FEITAS ANTES DE JULHO DE 1994 (REMUNOM, 2023)
The judgment of Theme 1.102 of the Federal Court of Justice on the Lifetime Review was perhaps themost awaited decision of the year 2022. The present work will discuss the historical scenario since theReal Plan, going by the advent of Law 9.876/99, which changed the wording of art. 29, I and II, of Law8.213/91, by Constitutional Amendment n. 103/2019 (EC 103/19), which dealt with the Social SecurityReform, until the publication of the judgment of the decision in 2023. Therefore, the entire analysis ofthe factual framework that the review is inserted in aims to verify whether there was a right violatedduring two decades of oppressed rights, given the non-accounting of social contributions prior to July1994 and which could have significantly increased the values received by policyholders. Thus, duringthe elaboration of the research, the deductive and historical methodology was adopted, analyzing thedoctrine and legislation, as well as observing an entire social context. Therefore, with the research itwas possible to confirm the possibility of including the contributions made prior to 1994 in the face ofthe favorable judgment to the insured.